CORPORATE SOCIAL RESPONSIBILITY TO REDUCE COMMUNITY REJECTION OF A COMPANY EXISTENCE: ANALYSIS OF BUSINESS ETHICS PERSPECTIVE - Sitti Faoziyah (Journal of Scientech Research and Development, 2022)
The purpose of this study was to investigate the role of corporate social responsibility (CSR) in reducing the impact of community rejection of the company's existence. In addition, this study was also conducted to explore CSR from the perspective of business ethics theory. The research location is the community in the area adjacent to PT. Pertamina (Persero) RU VI in Balongan Indramayu, West Java. The research method used is phenomenological-qualitative by investigating the experiences of the participants in depth. The focus of the research topics are CSR, rejection reduction, and business ethics. The findings reveal that Pertamina already has two flagship CSR programs that are currently being implemented and have had a positive impact on reducing public resistance to the company's existence. Through these CSR programs, Pertamina and the community within the company work together to achieve the success of the program. Thus, the company's commitment to CSR practices has reduced the impact of community rejection of the company. Interestingly, the local government also actively participates in the program. Unfortunately, the fire incident is contrary to Pertamina's commitment to pay attention to environmental impacts and the principle of honesty. And this is a serious concern considering the possible negative impacts it can cause. Second, viewed from the perspective of business ethics, Pertamina has implemented one of the principles of business ethics. Pertamina has built the values ​​of good business behavior. It's just that in the future it is necessary to improve other principles of business ethics, namely the principles of honesty, fairness, autonomy in order to create effective business ethics.